Photocatalytic hydrogen generation from a methanol–water mixture in the presence of g-C3N4 and graphene/g-C3N4. (20th October 2022) - Touati, Wassila; Karmaoui, Mohamed; Bekka, Ahmed; Edelmannová, Miroslava Filip; Furgeaud, Clarisse; Chakib, Alaoui; Allah, Imene kadi; Figueiredo, Bruno; Labrincha, J. A.; Arenal, Raul; Koci, Kamila; Tobaldi, David Maria
Abstract : Synthesis and application of g-C3 N4 and graphene/g-C3 N4 in H2 production from water splitting, using different g-C3 N4 precursors. Abstract : Graphitic carbon nitride (g-C3 N4 ), possessing high thermal and chemical stability, non-toxicity, facile synthesis, and low band gap energy is a promising candidate for photocatalytic applications. In this study, bulk and exfoliated g-C3 N4 were synthesised from different precursors (melamine and urea). Moreover, the surface of bulk g-C3 N4 and exfoliated g-C3 N4 was modified with graphene (0.5 wt% and 1 wt%) aiming to obtain a prolonged carrier lifetime. The effect of g-C3 N4 synthesis from various precursors and the influence of graphene content on the photocatalytic activity during the degradation of a water–methanol mixture under UVC irradiation were examined, in comparison to commercial P25. Hydrogen, methane and carbon monoxide were the decomposition products; hydrogen was the main product of decomposition, whereas CH4 and CO resulting from the reduction of CO2 were generated in a significantly smaller amount. All the produced photocatalysts, whether pure or modified with graphene, exhibited higher activity than the commercial photocatalyst P25.